Pengaruh Faktor dan Mekanisme Pengerasan Regangan pada Baja Hadfield - Haris Wahyudi; Tatacipta Dirgantara; Rochim Suratman; Aditianto Ramelan (Mesin, 2018)
Abstract. Hadfield steel has good toughness, ductility, impact resistance, wear resistance and has excellent work hardening. It has a carbon content of 1-1.4% and manganese 11-14% by weight, a ratio of approximately 1:10. The potential for increasing its strength against strain hardening can be seen from the wide range of plastic strength, 379 MPa yield strength and 965 MPa tensile strength. The hardening of Hadfield steel strain depends on the type loading which affect the dislocation slip mechanism, twinning deformation, and the interaction between slip and twinning. The study of high strain rates in Hadfield steel is quite interesting and still relevant to date, although there have been many papers published. Hadfield cast steel which has a relatively low hardness, can be increased its hardness by treatment and high work hardening (high strain rate). There are factors that influence the hardness of Hadfield steel include alloying, solid solution process and high work hardening. Nitrogen as austenite stabilizer is important for work hardening, chromium and vanadium are added to increase hardness because it will form carbides, and aluminum is added to increase wear resistance. High strain rate deformation is applied to provide improved strength because of propensity of twinning mechanism is likely to occur. Optimum strain hardening by twinning mechanism can only be achieved at critical impact energy. Explosive hardening generates small deformations but provides significant changes in mechanical properties.Abstrak. Baja Hadfield memiliki sifat ketangguhan, keuletan, ketahanan impak, ketahanan terhadap aus dan memiliki work hardening yang sangat baik. Memiliki kandungan unsur karbon 1-1,4% dan mangan 11-14% berat, rasio kurang lebih 1:10. Potensi peningkatan kekuatan terhadap pengerasan regangan, dapat dilihat dari rentang kekuatan plastis yang lebar, kekuatan luluh 379 MPa dan kekuatan tarik 965 MPa. Pengerasan regangan baja Hadfield tergantung kepada proses pembebanan melalui mekanisme slip dislokasi, deformasi twinning, serta interaksi antara slip dan twinning. Kajian tentang high strain rate pada baja Hadfield menjadi topik yang cukup menarik dan relevan, meskipun telah banyak publikasi yang dihasilkan. Baja Hadfield yang memiliki kekerasan relatif rendah, mampu ditingkatkan nilai kekerasannya melalui rekayasa perlakuan panas dan deformasi plastis secara cepat. Beberapa faktor yang mempengaruhi kekerasan baja Hadfield antara lain bahan paduan, perlakuan panas dan proses pengerasan regangan yang diberikan. Nitrogen sebagai penstabil austenit penting untuk pengerjaan dingin, kromium dan vanadium ditambahkan untuk meningkatkan kekerasan karena akan membentuk karbida, dan aluminum ditambahkan untuk meningkatkan ketahanan aus. Deformasi kecepatan regangan tinggi pada Hadfield memberikan peningkatan kekuatan lebih baik karena mekanisme twinning lebih dominan. Pengerasan regangan optimum oleh mekanisme twinning hanya dapat dicapai pada energi impak kritikal. Explosive hardening menghasilkan deformasi yang relatif kecil tetapi memberikan perubahan sifat mekanik yang signifikan.